دراسة الصفات المورفولوجية لبعض طرز الريحان (الآس) Myrtus communis المنتشرة في ناحية البهلولية – اللاذقية - رضوان, أسامة; سلمان, يحيى; ناصر, عمار (Latakia University Journal -Biological Sciences Series, 2017)
تمت الدراسة خلال عامي 2014– 2015 على أربعة طرز برية للريحان في عدة قرى تابعة لناحية البهلولية وهي : البهلولية ، فدره ، الكركيت ، برابشبو ، الزوبار ، هذه الطرز تتواجد على شكل تجمعات شجيرية ، هذه الطرز تختلف في العديد من الصفات المورفولوجية . الطراز الأول بري ذو ثمار ضامرة ،الطراز الثاني تميز بثماره ذات اللون الأسود المزرق، الطراز الثالث ذو ثمار كروية بيضاء ،الطراز الرابع ذو الثمار البيضاء المائلة للصفرة تتميز بشكلها المتطاول هذا الطراز يتفوق على باقي الطرز بأبعاد الثمرة ووزن مئة بذرة وكذلك بالوزن الرطب والجاف للأوراق وكذلك بسماكة الورقة ، هذا الطراز موجود في قرية برابشبو بشكل رئيسي ، لا توجد فروق معنوية بين الطرز الأربعة في أبعاد الورقة ، متوسط عدد الفروع الهيكلية على الساق هي (8) ثمانية فروع للطرز الأربعة ، بينما كان متوسط زاوية التفرع 79° . لا توجد فروق معنوية بين الطرز الأربعة في أبعاد الزهرة وعدد الأسدية في الزهرة وهي بالمتوسط (148) سداة . موعد بداية الإزهار للطرز هو بين( 11-7 ) من حزيران وبداية العقد بين (5 -1) من تموز، بينما كان موعد الإزهار الأعظمي للآس بين (20 -23) حزيران ، في حين موعد العقد الأعظمي بين (15-18) تموز . The study has been conducted out during the years 2014 - 2015 at four phenotypes in Al-Bahluliyah area ,it has been identified five villages belonging to Al-Bahluliyah is Al-Bahluliyah, Fedrah, Carket, Brabshbo, Alzubar, these models exist in the form of groups of shrubs , these models differ in many morphological characteristics. first phenotype with theatrophic fruits , the second phenotype has a bluish black fruits , third phenotype with spherical and white fruits , fourth phenotype with white fruits witch has long form this model is superior to the other of the models dimensions of the fruit and the weight of a hundred seeds , wet weight ,dry weight ,and thick leaf , this model is in the Brabshbo mainly village, there are not significant differences between the four models in the leaf dimensions .The average number of main branches is (8) , The average number of branching angle is (79°) . there are not significant differences between the four models in the flower dimensions and the number of stamens in the flower ,the number of stamens is (148) . the date of the beginning of the flowering of the models which is between ( 7-11 ) June and the beginning of the transformation to the fruits between( 1- 5)July. Maximum flowering date of the models which is between (20-23 ) June Maximum transformation date to the fruits between( 15- 18)July.